Softskill Base Arabic Language Teaching Model in Improving Talaqul Kalam for College Student in Universitas Sains Al-Quran Jawa Tengah Wonosobo - Asep Sunarko; Abdurrahman Masud; Subur Subur (ADP Publisher, 2024)
Arabic language learning has a major problem related to its renewal. Arabic language learning is always identical with grammatical (Qawa’id) aspects which seem to be rigid, complicated, and confusing. There are two major Arabic language learning orientations: as body of knowledge and mastery. The purpose of this research is to produce an Arabic language learning model based on soft skills to effectively improve the students’ Talaqah al kalaam at Universitas Sains Al-Qur’an (UNSIQ), Wonosobo, Central Java, Indonesia. This research was considered as a field study in the form of Research and Development (R&D) involving students from each faculty of Universitas Sains Al-Qur’an (UNSIQ), Wonosobo, Central Java, Indonesia. The research data were collected through observation, in-depth interview, questionnaire, test, and documentation. The collected data were then analyzed through several stages: (a) initial-product test analysis, (b) limited data trial result analysis, (c) extensive data trial result analysis, and (d) student learning response analysis. The research results showed that the Arabic language learning model based on soft skills had fulfilled the validity elements through Expert Judgment method and been considered very effective proven by the significant improvement in post-test results. This model was also proven practical proven by the test results showing that the supporting instruments, such as Course Learning Unit, Learning Module, Semester Learning Plan, Test Instrument, and Learning Implementation Sheet, were very good.